Geant4‐DNA example applications for track structure simulations in liquid water: A report from the Geant4‐DNA Project. Issue 8 (12th July 2018) - Incerti, S.; Kyriakou, I.; Bernal, M. A.; Bordage, M. C.; Francis, Z.; Guatelli, S.; Ivanchenko, V.; Karamitros, M.; Lampe, N.; Lee, S. B.; Meylan, S.; Min, C. H.; et al.
Abstract : This Special Report presents a description of Geant4‐DNA user applications dedicated to the simulation of track structures (TS) in liquid water and associated physical quantities (e.g., range, stopping power, mean free path…). These example applications are included in the Geant4 Monte Carlo toolkit and are available in open access. Each application is described and comparisons to recent international recommendations are shown (e.g., ICRU, MIRD), when available. The influence of physics models available in Geant4‐DNA for the simulation of electron interactions in liquid water is discussed. Thanks to these applications, the authors show that the most recent sets of physics models available in Geant4‐DNA (the so‐called "option4" and "option 6" sets) enable more accurate simulation of stopping powers, dose point kernels, and W‐values in liquid water, than the default set of models ("option 2") initially provided in Geant4‐DNA. They also serve as reference applications for Geant4‐DNA users interested in TS simulations.